T-cell infiltration in the central nervous system and their association with brain calcification in Slc20a2-deficient mice - Zhang, Yi; Ren, Yaqiong; Zhang, Yueni; Li, Ying; Xu, Chao; Peng, Ziyue; Jia, Ying; Qiao, Shupei; Zhang, Zitong; Shi, Lei (Frontiers in Molecular Neuroscience, 2023)
Primary familial brain calcification (PFBC) is a rare neurodegenerative and neuropsychiatric disorder characterized by bilateral symmetric intracranial calcification along the microvessels or inside neuronal cells in the basal ganglia, thalamus, and cerebellum. Slc20a2 homozygous (HO) knockout mice are the most commonly used model to simulate the brain calcification phenotype observed in human patients. However, the cellular and molecular mechanisms related to brain calcification, particularly at the early stage much prior to the emergence of brain calcification, remain largely unknown. In this study, we quantified the central nervous system (CNS)-infiltrating T-cells of different age groups of Slc20a2-HO and matched wild type mice and found CD45+CD3+ T-cells to be significantly increased in the brain parenchyma, even in the pre-calcification stage of 1-month-old -HO mice. The accumulation of the CD3+ T-cells appeared to be associated with the severity of brain calcification. Further immunophenotyping revealed that the two main subtypes that had increased in the brain were CD3+CD4-CD8- and CD3+CD4+ T-cells. The expression of endothelial cell (EC) adhesion molecules increased, while that of tight and adherens junction proteins decreased, providing the molecular precondition for T-cell recruitment to ECs and paracellular migration into the brain. The fusion of lymphocytes and EC membranes and transcellular migration of CD3-related gold particles were captured, suggesting enhancement of transcytosis in the brain ECs. Exogenous fluorescent tracers and endogenous IgG and albumin leakage also revealed an impairment of transcellular pathway in the ECs. FTY720 significantly alleviated brain calcification, probably by reducing T-cell infiltration, modulating neuroinflammation and ossification process, and enhancing the autophagy and phagocytosis of CNS-resident immune cells. This study clearly demonstrated CNS-infiltrating T-cells to be associated with the progression of brain calcification. Impairment of blood–brain barrier (BBB) permeability, which was closely related to T-cell invasion into the CNS, could be explained by the BBB alterations of an increase in the paracellular and transcellular pathways of brain ECs. FTY720 was found to be a potential drug to protect patients from PFBC-related lesions in the future.